Nutrition in burns: A practical solution to a difficult problem - Suri, M P; Patel, C K; Dhingra, VJ S; Raibagkar, S C; Mehta, D R (Indian Journal of Plastic Surgery, 2006)
The nutritional aspects of burns is an important but yet not properly looked after problem in the management of burns. We present our experience with dealing with such a problem giving a practical and easy to deliver solution to nutrition. Early enteral nutrition should be started with frequent assessment to the need of the patient and it requires a team approach.
Keywords: Burns; diet charts; enteral nutrition; nutrition; nasogastric tube; tube feeding